Synthesis and characterization of magnetic nanoparticles (mnps) coated with polypyrrole (ppy) for removal of 2,4-dinitrophenol (2,4-dnp) / Nor Azean Nadhirah Mohamed Sani - Mohamed Sani, Nor Azean Nadhirah (Faculty of Applied Sciences, 2017)
Magnetic nanoparticles coated with Polypyrrole (MNPs-PPy) was successfully synthesized in this study. The characterization of MNPs-PPy was determined by using Fourier Transform Infrared Spectroscopy (FTIR) analysis, Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD). MNP has been coated with PPy was shown by the results of FT-IR, SEM and XRD. The result of FT-IR has showed the peak of F e-O at 5 80 cm· 1. SEM result has showed the morphology of the surface of MNPs-PPy which have globular structure. In addition, XRD result has showed the MNPs-PPy is in the crystalline form. The removal efficiency was determined by using Ultra violet Visible Spectroscopy (UV -Vis). The synthesized MNPs-PPy was successfully removed the 2,4-Dinitrophenol (2,4- DNP) under several conditions. The first step is to determine the level of performance of the MNPs-PPy for the removal of 2,4-DNP. When the MNPs-PPy performance can reach up to 85 % removal, the next step can be proceed. The next step is to find the best condition for the removal to occur. There are several parameters that need to be done such as the effect pH, temperature and concentration, contact time, amount of adsorbent, interfering ions and reusability. The result showed 98.67 % removal ofanalyte at pH 6,318 K, 10 ppm analyte, 75 minutes and 50 mg of adsorbents.